Can PDSI inform extreme precipitation?: An exploration with a 500 year long paleoclimate reconstruction over the U.S. Issue 5 (22nd May 2016) - Steinschneider, Scott; Ho, Michelle; Cook, Edward R.; Lall, Upmanu
Abstract: This study explores whether it is possible to reconstruct the frequency of extreme precipitation occurrence across the contiguous United States (CONUS) using the Living Blended Drought Atlas (LBDA), a 500 year paleoclimate reconstruction of the summer (June–August) Palmer Drought Severity Index (PDSI). We first identify regions of the country where the LBDA may reflect the occurrence of extremes based on their seasonality and contribution to total annual moisture delivery. Correlation measures are used to assess the relationship between the frequencies of extreme precipitation occurrence and both the instrumental monthly PDSI and the annual LBDA‐estimated PDSI. Extreme precipitation is found to account for a large portion of total precipitation west of the Mississippi River and clusters in particular seasons (winter and summer), supporting a strong relationship with the LBDA without much information loss from the instrumental PDSI data. Dimension reduction techniques are used to explore the joint spatiotemporal structure of extreme precipitation occurrence and LBDA across the country. The primary modes of variability of the LBDA and extreme precipitation occurrence relate remarkably well for a region centered over the southwest that exhibits an ENSO‐like time‐frequency structure. Generalized linear models (GLMs) are used to demonstrate the feasibility of reconstructing the annual extreme precipitation frequency over the 500 year prehistoric record at two sites in the southwest and Southern Plains. GLM‐based reconstructions show a high degree of structured variability in the likelihood of extreme precipitation occurrences over the prehistoric record. Key Points: Extreme precipitation occurrence over the western U.S. relates well to a paleo‐reconstruction of PDSI The primary modes of variability for extreme precipitation occurrences and PDSI relate very well The risk of extreme precipitation occurrence can be reconstructed for individual sites